Gender Representation Within Communication among Officials at State Islamic University in Indonesia - Elfi Yanti Ritonga; Syafaruddin Ritonga (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
This research aims to see gender representation within communication among officials in State Islamic University in Indonesia and how women occupying structural positions at State Islamic University in Indonesia are viewed. This is qualitative descriptive research carried out in UIN Sunan Ampel Surabaya, UIN Maulana Malik Ibrahim Malang, UIN Sultan Maulana Hasanuddin, and UIN Syarif Hidayatullah Jakarta. Data were obtained from observation and interviews.Â  The theory used in this study follows Max Weber's bureaucratic theory regarding gender representation in organizational communication, namely the existence of authority, specialization and regulations in organizations (universities). This is in accordance with research findings that the bureaucracy of UIN Sunan Ampel Surabaya, UIN Maulana Malik Ibrahim Malang, UIN Sultan Maulana Hasanuddin and UIN Syarif Hidayatullah Jakarta in accordance with Max Weber's theory has fulfilled the characteristics of bureaucracy, namely having authority or power, specialization in the division of work (fields) without distinguishing between men and women, and there are regulations that all university personnel must obey. The most important results of this study include are: (1) there is representation of women occupying structural positions in higher education, (2) women have the right to occupy structural positions in higher education based on their ability; (3) there is no differentiation in communication between men and women who hold positions in universities; (4) communication among officials in universities prioritizes integrity, friendship, kinship, responsibility and professionalism without discriminating gender and positions (members or leaders).